An Exploratory Study of Organizational Justice and Work Attitudes Among Chinese Prison Staff - Lambert, Eric G. (The prison journal, 2018)
While both forms of organizational justice are important, the empirical literature indicates that procedural justice generally has wider and greater effects on job attitudes compared with distributive justice. Regression analysis of self-reported survey data from 322 staff at two Chinese prisons in Guangzhou suggests that, while both forms of organizational justice were important for Chinese correctional staff’s organizational commitment, distributive (but not procedural) justice had significant positive associations with both job involvement and job satisfaction. This emphasis on distributive justice differs from what has been empirically found for U.S. correctional staff.